FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI KELAPA SAWIT DI PT PERKEBUNAN NUSANTARA XIII - Alfonsius Dedeo Raden Mas; Dewi Kurniati; Marisi Aritonang (Universitas Galuh, 2023)
The total production of oil palm plantations at PT PN 13 during the period 2018 to 2021 fluctuated in each plantation. The causes of fluctuations or declines and increases in the number of oil palms are due to several factors including internal factors such as the age of the plants that are old, the number of plant populations that are not large enough and the application of fertilizers is not appropriate at the dose and time. While the external factor is due to the influence of erratic rainy weather. The purpose of this research is to analyze the effect of land area, labor, number of trees, plant age, NPK fertilizer, super dolomite fertilizer, and pesticides on oil palm production at PT PN 13. Data were collected through interviews and documentation of 13 plantations. taken from the period 2018 to 2021. The data analysis technique was carried out using the panel data regression method. The result of the chosen approach model is the fixed effect (FEM) model. So the factors that have a significant influence are the number of trees, NPK fertilizers, super dolomite fertilizers, and pesticides. For factors that have no significant effect are land area, labor, and plant age.